2017
DOI: 10.1080/21655979.2017.1297347
|View full text |Cite
|
Sign up to set email alerts
|

Development of CRISPR/Cas9 mediated virus resistance in agriculturally important crops

Abstract: Clustered regulatory interspaced short palindromic repeats (CRISPR)/CRISPR associated nuclease 9 (Cas9) system of targeted genome editing has already revolutionized the plant science research. This is a RNA guided programmable endonuclease based system composed of 2 components, the Cas9 nuclease and an engineered guide RNA targeting any DNA sequence of the form N20-NGG for novel genome editing applications. The CRISPR/Cas9 technology of targeted genome editing has been recently applied for imparting virus resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 24 publications
0
31
0
Order By: Relevance
“…For example, an SaCas9/gRNA system was programed to speci cally target HIV-1 provirus and suppress HIV-1 infection in Jurkat C11 cells [15]. CRISPR/Cas9 was also employed to target plant viruses, which provided a more versatile viral resistance in important crops [16]. Class II CRISPR systems include Cas13a other than cas9 [17].…”
Section: Introductionmentioning
confidence: 99%
“…For example, an SaCas9/gRNA system was programed to speci cally target HIV-1 provirus and suppress HIV-1 infection in Jurkat C11 cells [15]. CRISPR/Cas9 was also employed to target plant viruses, which provided a more versatile viral resistance in important crops [16]. Class II CRISPR systems include Cas13a other than cas9 [17].…”
Section: Introductionmentioning
confidence: 99%
“…Novel therapeutic strategies are urgently required to treat such infectious viruses. Since its discovery, the CRISPR/Cas9 system has been developed into a multifunctional genetic modification tool, which can now be used to perform gene deletion, gene insertion, genome‐wide screening, gene therapy and genetic breeding (Khatodia et al , ; Ledford, ; Zhang et al , ; Gebre et al , ). In previous studies, we demonstrated that the system can effectively edit the BmNPV genome by targeting the ie‐1 gene, thereby inhibiting the viral DNA replication in vivo and in vitro (Dong et al , ; Dong et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…The CRISPR/Cas9 tools for key genome editing are currently applied for reporting virus resistance in the plants [23]. CRISPR-Cas9 is an RNA directed DNA endonuclease organization, which comprises of Cas9 nuclease showing limited targeting bases through protospacer end-to-end motif complexed by simply customizable sole controller RNA targeting about 20-bp genomic arrangement.…”
Section: Global Perspective On Pharmaceuticals Bioengineered Toolsmentioning
confidence: 99%